DORĘCZENIE PISMA DOROSŁEMU DOMOWNIKOWI W POSTĘPOWANIACH SĄDOWYCH I ADMINISTRACYJNYCH - Gapska, Edyta; Gapski, Maciej P. (Zeszyty Prawnicze, 2016)
Service of Documents on an Adult Household Member in Judicial and Administrative Proceedings All proceedings contain a set of rules regarding the service of process. This general procedural institution varies from one case to another, although the aim and function is always the same. One of the differences involves substituted service of documents when the party to be served is unavailable for personal service. In such a situation substituted service allows the server to deliver documents to the address of the person to be served to an adult household member. Each jurisdiction requires that it should be a responsible individual of a suitable age and discretion who guarantees that the addressee will receive the documents served. The paper shows differences in interpretation and application of the substitute service of documents in civil, criminal, administrative and tax proceedings, despite their functional and terminological similarity. In particular divergences concern the meaning of the term “adult,” which is not synonymous with the juridical term “major”. Neither is there a uniform definition of what is meant by the addressee being “unavailable” for personal service or how his substitute should confirm that he has accepted the duty of bringing the documents to the addressee’s notice. The conclusion indicates the need for clarification and unification of the regulations analysed in the article.